Transfer Methods of Graphene from Metal Substrates: A Review. Issue 7 (18th April 2019) - Ma, Lai‐Peng; Ren, Wencai; Cheng, Hui‐Ming
Abstract: Graphene synthesized by chemical vapor deposition (CVD) on metal substrates has attracted tremendous attention due to its high growth‐quality, scalability, and high structural tunability, which holds great promise in a wide range of applications. In most cases, CVD graphene on metals must be transferred to target substrates and the intact/clean and efficient transfer of large‐area graphene remains challenging, thus greatly hindering the practical applications of CVD‐grown graphene in high‐performance devices. Here, the representative methods of transferring CVD graphene are discussed from the perspective of their impacts on the structural integrity and contamination of graphene as well as their scalability. Particularly, the principles, advantages, and limitations are highlighted in various methods. Abstract : Representative methods of transferring graphene from metal substrates are discussed from the perspective of their impacts on the structural integrity and contamination of graphene as well as their scalability. These methods are classified into two categories, etching and etching‐free transfer, according to different principles of separating graphene from metals. Moreover, large‐area transfer methods will be discussed separately.